APLIKASI METODE ELEMEN HINGGA PADA PERANCANGAN POROS BELAKANG GOKAR LISTRIK - Henra Heny Sigarlaki; Stenly Tangkuman; Tritya A R Arungpadang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
ABSTRACT Today, Society needs a vehicle a simple , inexpensive and environmentally friendly. One alternative option is an electric gokart. In the electric gokart are a rear axle which serves to move the power and spin that comes from the electric motor to the rear wheels so as to allow an electric go-karts can run. The aim of this study as follows : First, create a simulation of the finite element method with SolidWorks software to get the voltage and the maximum deflection caused by the load . Second, making calculations manually finite element method to validate the simulation results with SolidWorks software. Third , get the dimensions of the shaft for electric gokart designed by the Department of Mechanical Engineering University of Samratulangi Manado. Finite element method simulations with SolidWorks software has gained maximum voltage results 120,212x106 Pa., and the maximum deflection of 0.00051 mm. While the manual calculation values ​​obtained displacement / maximum displacement is 0.00045 mm. Besides the results also indicate that the maximum displacement occurs at the same location or point. Thus , the simulation results have been validated by using the results of manual calculations. The dimensions of the design is the diameter of the shaft 20 mm and a length of 1000 mm. Key word: Gokart, Finite Element Method, Simulation.